Lung adenocarcinoma with KRAS-Q61H: clinicopathologic features, diagnostics, and the evolving treatment landscape - Serafimidis, Ioannis (Frontiers in Oncology, 2026)
KRAS is one of the most frequently mutated oncogenes in lung adenocarcinoma (LUAD), with the KRAS-Q61H mutation representing a rare but biologically distinct subgroup. Although KRAS-Q61H is associated with more aggressive clinical behavior, including advanced-stage disease at diagnosis and atypical metastatic spread, its molecular characteristics are not fully understood. This mutation preferentially activates the RAF-MEK-ERK pathway and has been shown to exhibit relative independence from upstream signaling factors like SHP2 and SOS1, distinguishing it from other KRAS mutations. KRAS-Q61H is frequently co-mutated with TP53, and this co-alteration has been linked to increased genomic instability, invasion, and metastatic potential, particularly peritoneal dissemination, which is a feature shared with other cancers harboring KRAS-Q61H, such as pancreatic ductal adenocarcinoma (PDAC) and colorectal cancer (CRC). Comprehensive molecular profiling, including next-generation sequencing (NGS) and plasma-based liquid biopsy, is critical for the early detection of KRAS-Q61H and its co-mutations, enabling more personalized treatment approaches. Despite the lack of approved allele-specific therapies, emerging treatment strategies targeting the MAPK pathway, SHP2, SOS1, and pan-KRAS inhibitors offer hope for more effective management. This review provides an in-depth analysis of the clinical, molecular, and therapeutic aspects of KRAS-Q61H LUAD, with a particular focus on its metastatic behavior, the impact of co-mutations, and the urgent need for molecular profiling in guiding treatment decisions.